Cooper, Hewitt & Company (Ringwood, N.J.) records - Cooper, Hewitt & Company (Ringwood, N.J.)
Business records of the iron works and glue factory at Ringwood, N.J., of Peter Cooper and Abram Hewitt.
Finding aid available in the Library of Congress Manuscript Reading Room.
Keywords: Cooper, Peter, -- 1791-1883.; Hewitt, Abram S. -- 1822-1903.; Adhesives industry -- New Jersey -- Ringwood; Glue; Iron industry and trade -- New Jersey -- Ringwood